A leaflet plication clip is an effective surgical template for mitral valve foldoplasty. (6th December 2017) - Wamala, Isaac; Saeed, Mossab; Ghelani, Sunil J; Gauvreau, Kimberlee; Hammer, Peter E; Vasilyev, Nikolay V; del Nido, Pedro J
Abstract: OBJECTIVES: During mitral valve repair using the foldoplasty technique, correct judgement of the necessary dimensions and orientation of the leaflet fold is a critical but challenging step that can affect the chances of successful repair. In this study, we investigated whether a leaflet plication clip can be used to guide suture foldoplasty for posterior leaflet prolapse of the mitral valve. METHODS: Complete posterior leaflet prolapse was created in both in vivo and ex vivo pig hearts by severing the chordae supporting the middle scallop. A plication clip was applied to perform leaflet foldoplasty. Sutures were then placed using the clip as a template and the clip was removed. Leaflet width after flail creation, clip application and suture placement was determined in an ex vivo test. In vivo repair and evaluation was then performed in 7 pigs to determine the repair efficacy under normal physiological loading, at 1 and 6 h after recovery from cardiopulmonary bypass. RESULTS: Leaflet width after suture placement was comparable to the clip alone (7.0 ± 1.4 vs 9.0 ± 1.6) and both were significantly less than the flail width 15.7± 2.5 mm. In vivo, average coaptation height following repair was restored to 4.7 ± 1.4 mm and 4.2 ± 1.3 mm at 1 and 6 h, respectively, after recovery compared with the baseline height of 5.5 ± 0.9 mm. Mitral regurgitation was reduced from moderate–severe to mild or less, and addition of a De-Vega annuloplasty in the last 3 animals abolished residual leaks to trivial or none. CONCLUSIONS: Application of the adjustable leaflet plication clip facilitated accurate determination of the correct position, width, height and orientation of the foldoplasty. Any necessary clip repositioning was made prior to the placement of sutures avoiding the need to redo the sutures. This approach could potentially help improve the ease and reproducibility of the foldoplasty repair.